Efficient algorithms for the reliability optimization of tall buildings - Spence, S.M.J.; Gioffrè, M. (Journal of wind engineering and industrial aerodynamics, 2011)
Modern tall buildings are often characterized by their slenderness and sensitivity to extreme wind events. For these buildings traditional least weight optimization procedures based on a few idealized equivalent static wind loads derived from directionless wind models may be inadequate. This is especially true considering traditional models used for combining aerodynamics and site specific climatological information. Indeed these methods were developed for buildings with statistically and mechanically uncoupled systems exhibiting strong preferential behavior for certain wind directions. Using these models during a traditional deterministic optimization may lead to unsafe designs. In this paper a recently developed component-wise reliability model is used to rigorously combine the directional building aerodynamics and climatological information. An efficient reliability-based design optimization scheme is then proposed based on decoupling the traditionally nested optimization loop from the reliability analysis. The decoupling is achieved by assuming the level cut sets containing the mean wind speeds generating a response with specified exceedance probability independent of changes in the design variable vector. The decoupled optimization problem is solved by defining a series of approximate explicit sub-problems in terms of the second order response statistics of the constrained functions.